2021
DOI: 10.3389/fphys.2021.642752
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Angiotensin II Infusion Induces Oxidative and Endoplasmic Reticulum Stress and Modulates Na+ Transporters Through the Nephron

Abstract: High plasma angiotensin II (Ang II) levels are related to many diseases, including hypertension, and chronic kidney diseases (CKDs). Here, we investigated the relationship among prolonged Ang II infusion/AT1 receptor (AT1R) activation, oxidative stress, and endoplasmic reticulum (ER) stress in kidney tissue. In addition, we explored the chronic effects of Ang II on tubular Na+ transport mechanisms. Male Wistar rats were subjected to sham surgery as a control or prolonged Ang II treatment (200 ng⋅kg–1⋅min–1, 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…AT1-mediated oxidative stress injury has been extensively reported in the literature. 25,26 Our experiment provided compelling evidence that AT1 was highly expressed in intestinal epithelial mucosa, and its mediated oxidative stress response was involved in intestinal mucosal barrier injury. At the same time, it was observed that by inhibiting AT1, the expression of TJ protein, GSH and SOD in intestinal mucosa epithelium were improved.…”
Section: Discussionmentioning
confidence: 75%
“…AT1-mediated oxidative stress injury has been extensively reported in the literature. 25,26 Our experiment provided compelling evidence that AT1 was highly expressed in intestinal epithelial mucosa, and its mediated oxidative stress response was involved in intestinal mucosal barrier injury. At the same time, it was observed that by inhibiting AT1, the expression of TJ protein, GSH and SOD in intestinal mucosa epithelium were improved.…”
Section: Discussionmentioning
confidence: 75%
“…CysC is a cysteine proteinase inhibitor that might aid in overcoming some of the limitations related to the use of Cr serum levels for the estimation of GFR. Moreover, these levels are less dependent on body mass, nutritional status, or age [ 50 , 51 ]. However, the relatively high cost of measuring CysC, when compared to Cr, contributes to its still limited use in routine clinical practice.…”
Section: Diagnosismentioning
confidence: 99%
“…Different pathologies, such as diabetes mellitus [ 340 ], obesity [ 341 , 342 ], cardiovascular disease [ 343 , 344 ] and CKD [ 345 , 346 ], have been associated with ER stress. In CRS, the activation of ER stress in the heart and kidney could be induced by different factors, such as hemodynamic changes, hormones from the RAAS, inflammation or oxidative stress [ 346 , 347 , 348 ].…”
Section: Mechanisms Involved In Fibrosis Progressionmentioning
confidence: 99%
“…Different pathologies, such as diabetes mellitus [ 340 ], obesity [ 341 , 342 ], cardiovascular disease [ 343 , 344 ] and CKD [ 345 , 346 ], have been associated with ER stress. In CRS, the activation of ER stress in the heart and kidney could be induced by different factors, such as hemodynamic changes, hormones from the RAAS, inflammation or oxidative stress [ 346 , 347 , 348 ]. These pathophysiological mediators could directly induce ER stress in the myocardium or renal parenchyma, resulting in apoptotic cell death due to prolonged UPR activation [ 349 , 350 , 351 ] and the consequent fibrotic wound formation, all of which would eventually lead to structural and functional changes [ 348 , 352 , 353 , 354 ].…”
Section: Mechanisms Involved In Fibrosis Progressionmentioning
confidence: 99%